Effects of commercial formaldehyde inclusion and lysine level on nursery pig performance - Sica, L. G.; Cochrane, R. A.; Woodworth, Jason C.; Dritz, Steven S.; Stark, Charles R.; Jones, Cassandra K. (My University, 2016)
Previous research has demonstrated that commercial formaldehyde products may reduce the risk of microbiological hazards in feed, but there is concern about the product binding Lys and reducing growth performance. Therefore, the objective of this experiment was to evaluate the role of 2 commercially-available formaldehyde sources on growth performance of pigs fed a Lys-sufficient or Lys-deficient diet. A total of 299 pigs (PIC 327 × 1050; initial BW 15.2 kg) were used in a 14-d study. Dietary treatments were arranged in a 3 × 2 factorial design with 3 formaldehyde inclusions: none vs. 3.25 kg per tonne SalCURB (Kemin Industries, Inc., Des Moines, IA) vs. 3.0 kg per tonne Termin-8 (Anitox Corp, Lawrenceville, GA) and 2 Lys levels: Adequate (1.25% SID Lys) vs. Low (1.10% SID Lys). Product concentrations were established from supplier recommendations, and diets were treated with in commercial mills utilizing supplier-specific equipment. Pens of pigs were balanced by initial BW and randomly allotted to treatments with 5 pigs per pen and 10 pens per treatment. Data were analyzed in a factorial design using the GLIMMIX procedure of SAS. Overall, there was a tendency (P < 0.10) for a formaldehyde source × Lys level interaction to affect ADG and G:F. Pigs fed adequate Lys levels treated with no formaldehyde or SalCURB tended to have improved (P < 0.10) ADG and G:F compared to pigs fed adequate Lys levels treated with Termin-8. Pigs fed diets with low Lys and treated with Termin-8 tended to have poorer (P < 0.10) G:F than all other treatments. Regardless of source or Lys level, the inclusion of formaldehyde in nursery pig diets tended to reduce (P < 0.10) ADG and resulted in poorer (P < 0.05) G:F. Furthermore, the main effect of formaldehyde source affected (P < 0.05) ADG, G:F, and tended to affect (P < 0.10) ADFI, with pigs fed Termin-8 performing poorer than those fed SalCURB or no formaldehyde. As expected, Lys level affected (P < 0.05) ADG and G:F, but did not alter ADFI (P > 0.10). In summary, SalCURB inclusion did not alter nursery pig growth performance compared to the untreated basal diet, regardless of Lys level. However, the inclusion of Termin-8 tended to result in poorer G:F in adequate Lys diets and poorer ADG and G:F in low Lys diets compared to an untreated control.
Citation: Sica, L. G., Cochrane, R. A., Woodworth, J. C., Dritz, S. S., Stark, C. R., & Jones, C. K. (2016). Effects of commercial formaldehyde inclusion and lysine level on nursery pig performance. Journal of Animal Science, 94, 191-192. doi:10.2527/msasas2016-410
Keywords: Formaldehyde; Lysine; Nursery Pigs; Agriculture